Facile preparation of EDTA‐functionalized chitosan magnetic adsorbent for removal of Pb(II). Issue 32 (15th May 2015) - Tan, Zhengyan; Peng, Hong; Liu, Hongfang; Wang, Linling; Chen, Jing; Lu, Xiaohua
ABSTRACT A novel magnetic adsorbent (EDTA/chitosan/PMMS) was facilely prepared by reacting chitosan with EDTA anhydride in presence of PEI‐coated magnetic microspheres. The as‐synthesized EDTA/chitosan/PMMS was characterized by XRD, SEM, TGA, FT‐IR, and VSM, and then employed in removal of heavy metals of Pb(II) from aqueous solution. The results of the batch adsorption experiments revealed that the adsorbents had extremely high uptake capacities for Pb(II) in the pH range of 2 to 5.5, and the adsorption kinetics for EDTA/chitosan/PMMS was consistent with the pseudo–second‐order kinetic model. Moreover, its equilibrium data were fitted with the Langmuir isothermal model well, which indicated that the adsorption mechanism was a homogeneous monolayer chemisorptions process. The maximum adsorption capacity of EDTA/chitosan/PMMS for Pb(II) was found to be 210 mg g−1 at pH 4 (30°C), and further reuse experiments results suggested that EDTA/chitosan/PMMS could be a potential recyclable magnetic adsorbent in the practical wastewater treatment. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42384.